Free market madness and human nature. Issue 1 (9th February 2015) - Aydin, Necati
Abstract : Purpose: – This paper aims to discuss the crises of free market capitalism in terms of its understanding of human nature. It reveals how recent market madness can be attributed to certain elements of human nature. Design/methodology/approach: – The paper uses a conceptual and philosophical approach to analyze crises of free market capitalism. It links both success and failure of capitalism to its understanding of human nature. It compares and contrasts economic assumptions of human nature in conventional and Islamic economics. It attempts to explain the 2008 financial crisis through a comprehensive theory of human nature. Findings: – It sheds some light on the irrational aspect of human nature as the driving factor behind the 2008 financial crisis. It elaborates on the importance of knowing self for knowing human decisions in free market economy. It concludes with the need for a comprehensive theory of human nature to predict and prevent irrational and irresponsible behaviors of populist politicians, greedy capitalists and conspicuous consumers. The paper also reflects on the 2013 Nobel Prize in economics as a victory for the study of human nature. Originality/value: – The paper offers a new perspective to understand crises of free market capitalism.